Spatially and cell-type resolved quantitative proteomic atlas of healthy human skin - Beatrice Dyring-Andersen; Marianne Bengtson Løvendorf; Fabian Coscia; Alberto Santos; Line Bruun Pilgaard Møller; Ana R. Colaço; Lili Niu; Michael Bzorek; Sophia Doll; Jørgen Lock Andersen; Rachael A. Clark; Lone Skov; et al. (Nature Communications, 2020)
The human skin is a highly complex organ comprising multiple tissue layers and diverse cell types. Here, the authors present a spatially-resolved quantitative proteomic atlas of the healthy human skin, characterizing the protein profiles of four skin layers and nine cell types.